Preparation method of CO2 adsorbent Li4SiO4 ceramic pellets
The preparation of Li4SiO4 ceramic spheres by suspension curing method solves the problem that Li4SiO4 spheres are easy to elute in the circulating fluidized bed, achieving efficient CO2 adsorption performance and good spherical shape, and reducing the preparation cost.
Patent Information
- Application Number
- CN202411576060.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-10
AI Technical Summary
The existing Li4SiO4 pellets are easily eluted in the circulating fluidized bed, resulting in increased losses, and the preparation process has problems such as high equipment costs, environmental pollution and low yields.
Li4SiO4 ceramic spheres were prepared by suspension curing method. By mixing Li4SiO4 powder, LiOH·H2O powder and sodium water glass with deionized water, drip into polyethylene glycol to cure, and obtain porous structures after secondary curing and sintering. Small balls avoid elution and improve CO2 adsorption performance.
The good spherical shape and high CO2 adsorption performance of Li4SiO4 spheres are achieved, which avoids elution loss, reduces preparation cost, and improves the molding efficiency of the adsorbent.
Smart Images

Figure CN119281287A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of CO2 solid adsorbents, and in particular to a method for preparing CO2 adsorbent Li4SiO4 ceramic pellets. Background Art
[0002] The greenhouse effect is one of the main reasons for the rise in global temperatures and threats to human survival and health. CO2, as the "culprit" of the greenhouse effect, is mainly produced by the combustion of fossil fuels (such as coal, oil and natural gas) in industrial production processes and the emission of automobile exhaust. Since it takes a certain time span for clean energy to replace fossil energy, and some special fields (such as cement, aviation, etc.) are still difficult to get rid of their dependence on fossil energy. Therefore, CO2 capture, storage and utilization technology (CCUS) is the key. Among them, CO2 capture technology is crucial as the first link.
[0003] Source control is the best choice for achieving efficient capture of CO2. At present, the more mature CO2 source capture technologies include liquid amine absorption, membrane separation, and solid adsorption. In comparison, the solid adsorption method has attracted much attention due to its wide application temperature window, small cyclic adsorption and desorption losses, good high-temperature stability, and low cost. The more mainstream solid adsorbents include CaO, Li2ZrO3, Li4SiO4, KNaTiO3, etc. Among them, Li4SiO4 has the advantages of high adsorption capacity (theoretical adsorption capacity is 36.67%), good thermal stability, fast adsorption and desorption rate, and low regeneration temperature. In recent years, it has become one of the preferred materials for high-temperature CO2 adsorbents. The chemical reaction process of Li4SiO4 adsorption and desorption of CO2 is shown in reaction equations (1,2).
[0004]
[0005] At the same time, Li4SiO4 also has some problems that need to be solved urgently, such as the insignificant adsorption effect on low-concentration CO2, the adsorption activity still needs to be improved, and the grains are easy to grow during sintering. The most critical thing is that the mainstream Li4SiO4 powder adsorbent is easy to elute when reacting with CO2 in a circulating fluidized bed, which increases the loss of Li4SiO4. Designing Li4SiO4 into a spherical shape can avoid elution while increasing the reaction specific surface area.
[0006] At present, the preparation methods of Li4SiO4 pellets include melt spraying, extrusion-spheronization, sol-gel, wet chemical method, etc. Among them, the melt spraying process is simple, and the prepared pellets have high density and good sphericity, but the equipment cost is high, and it is necessary to use an expensive platinum crucible as a melt. At the same time, the pellets prepared by the melt spraying method will cause internal stress concentration of the material due to rapid cooling, resulting in microcracks and reducing its mechanical strength. The extrusion-spheronization method can realize the batch production of pellets, with low equipment cost and high pellet strength, but the sphericity is poor and the yield is low. The pellets prepared by the sol-gel method and the wet chemical method have high sphericity and high strength, but organic matter needs to be added during the preparation of the pellets, which is easy to cause environmental pollution and has a low yield. Therefore, it is urgent to develop a new method for preparing CO2 solid adsorbent pellets. Summary of the invention
[0007] The present invention provides a method for preparing CO2 adsorbent Li4SiO4 ceramic beads to solve the above problems.
[0008] The technical solution adopted by the present invention is: a method for preparing CO2 adsorbent Li4SiO4 ceramic balls, the method comprising at least the following steps:
[0009] S1: taking a certain mass of raw materials, the raw materials comprising a certain mass ratio of Li4SiO4 powder, LiOH·H2O powder, sodium water glass, and deionized water, and mixing the raw materials to obtain a slurry;
[0010] S2: dripping the slurry obtained in step S1 into polyethylene glycol, and obtaining green pellets after high-temperature curing;
[0011] S3: placing the mixture of the green pellets and polyethylene glycol in a constant temperature environment for secondary curing, and then filtering and washing to obtain reinforced green pellets;
[0012] S4: The reinforced green pellets obtained in step S3 are dried in the shade and sintered to obtain CO2 adsorbent Li4SiO4 ceramic pellets.
[0013] Preferably, in step S1, the mass ratio of Li4SiO4 powder, LiOH·H2O powder, sodium water glass and deionized water is 10:(3-4.6):(4-8):(4-7), and the LiOH·H2O powder in the raw material is obtained by sieving with 200 mesh.
[0014] Preferably, in step S1, Li4SiO4 powder, LiOH·H2O powder and sodium water glass are added to deionized water and stirred evenly to obtain suspension 1, and then the suspension 1 is added to a ball mill for ball milling at a speed of 200 r / min for 1 to 2.5 h to obtain a slurry.
[0015] Preferably, the polyethylene glycol in step S2 is placed in a constant temperature open container and is in a stirring state, the temperature is 50-80°C, the rotation speed is 300r / min, and then each drop of slurry with a volume of 0.03-0.04ml is dripped into the polyethylene glycol, and the vertical distance between the slurry drop and the top of the container is 3-4cm. After the dripping is completed, the green pellet is obtained by keeping warm for 5min.
[0016] Preferably, in step S3, the mixture containing green pellets and polyethylene glycol is placed in a culture dish and secondary cured in a 50° C. constant temperature drying oven for 40 to 50 hours to obtain reinforced green pellets.
[0017] Preferably, in step S3, the reinforced green pellets are washed with anhydrous ethanol and then dried in the shade at 15-25°C. The dried reinforced green pellets are then sintered in a box furnace, heated to 700°C at 5°C / min, and kept warm for 1.5-2.5h to obtain CO2 adsorbent Li4SiO4 ceramic pellets.
[0018] Preferably, the method for preparing the Li4SiO4 powder comprises the following steps:
[0019] Q1: LiOH·H2O and nano-SiO2 were mixed with deionized water in a certain mass ratio, and then added into a ball mill for 2 h to obtain suspension 2;
[0020] Q2: The suspension 2 is placed in a constant temperature drying oven at a temperature of 80-90°C for 30-40 hours to obtain Li4SiO4 precursor powder;
[0021] Q3: Place the Li4SiO4 precursor powder in a box furnace, heat it to 700℃ at 5℃ / min and keep it warm for 2h to obtain Li4SiO4 powder.
[0022] Preferably, in step Q1, the mass ratio of LiOH·H2O to nano-SiO2 is 7.35:2.5.
[0023] Preferably, in step Q1 and step S1, the ball-to-material mass ratio in the ball mill is 2:1, and the ball mill speed is 200 r / min.
[0024] Preferably, the Li4SiO4 powder is obtained by sieving through a 200-mesh sieve.
[0025] Compared with the prior art, the present invention has the following advantages: (1) The present invention proposes a method for preparing CO2 adsorbent beads by suspension solidification, wherein Li4SiO4 powder, LiOH·H2O powder, sodium water glass and deionized water are used as raw materials, and after mixing, they are dripped into polyethylene glycol for solidification to obtain adsorbent green pellets, which are then sintered to obtain porous Li4SiO4 ceramic pellets, which have good sphericity and good adsorption of CO2. (2) The sodium water glass added in the method is beneficial to the solidification of the Li4SiO4 green pellets due to the cross-linking reaction of SiO2 in its components, and on the other hand, due to the component Na + Solid solution enters the Li4SiO4 lattice to form Li3NaSiO4, which reacts with CO2 to form Li2SiO3 and Li2CO3 and Na2CO3 eutectic. The eutectic is easy to soften at low temperature, which promotes the diffusion of CO2 from the surface of the adsorbent to the inside, and improves the CO2 adsorption performance of the adsorbent. In addition, sodium water glass is used as a binder to improve the molding efficiency of the small balls. (3) Compared with Li4SiO4 powder, by making the adsorbent into a sphere, the elution of the adsorbent during the fluidized bed reaction is avoided, and the reaction specific surface area is increased, thereby improving the CO2 adsorption performance; (4) The preparation method of the present invention is simple and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD of CO2 adsorbent Li4SiO4 ceramic powder of Examples 1 to 5 of the present invention;
[0027] Figure 2 Surface SEM of CO2 adsorbent Li4SiO4 ceramic spheres prepared in Example 4 of the present invention;
[0028] Figure 3 This is a cross-sectional SEM of the CO2 adsorbent Li4SiO4 ceramic sphere prepared in Example 4 of the present invention;
[0029] Figure 4 The adsorption curves of the CO2 adsorbent Li4SiO4 ceramic balls prepared by the Li4SiO4 powder of the present invention and Example 2 and Example 4 under pure CO2 atmosphere;
[0030] Figure 5 BET adsorption-desorption curves of the Li4SiO4 powder of the present invention and the CO2 adsorbent Li4SiO4 ceramic spheres prepared in Example 2 and Example 4;
[0031] Figure 6 This is the actual CO2 adsorbent Li4SiO4 ceramic ball prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] In order to better illustrate the present invention, it is further described in conjunction with examples.
[0033] A method for preparing CO2 adsorbent Li4SiO4 ceramic beads, the method comprising at least the following steps:
[0034] S1: Take a certain mass of raw materials, the raw materials include Li4SiO4 powder, LiOH·H2O powder, sodium water glass, deionized water, the mass ratio is 10:(3-4.6):(4-8):(4-7), wherein the LiOH·H2O powder is obtained by sieving with 200 mesh. Add Li4SiO4 powder, LiOH·H2O powder and sodium water glass into deionized water, stir evenly to obtain suspension 1, then add suspension 1 into a ball mill for ball milling, the speed of ball milling is 200r / min, the time is 1-2.5h, and slurry is obtained;
[0035] S2: Polyethylene glycol is placed in a constant temperature open container and is in a stirring state, the temperature is 50-80°C, the speed is 300r / min, and then the slurry is dripped into the polyethylene glycol, the vertical distance between the slurry drop and the top of the container is 3-4cm, the volume of each drop of slurry is 0.03-0.04ml, the slurry drop is formed into balls under the action of the surface tension and shear force of the polyethylene glycol, and then under the heating action of the constant temperature open container, the sodium water glass is dehydrated due to the strong water absorption of polyethylene glycol, and SiO2 is cross-linked and cured, so the green blank ball can be obtained after keeping warm for 5 minutes. Among them, the constant temperature container is not specifically limited, and can preferably be a beaker placed on a constant temperature stirrer, the beaker capacity is 200ml, and the volume of polyethylene glycol in the beaker is 200ml. When dropping, the distance between the slurry and the beaker mouth is 3-4cm to ensure the sphericity of the formed balls;
[0036] S3: placing a mixture of green pellets and polyethylene glycol in a culture dish, and placing the culture dish in a 50° C. constant temperature drying oven for secondary curing for 40 to 50 hours to obtain reinforced green pellets;
[0037] S4: The reinforced green pellets are washed with anhydrous ethanol to remove the polyethylene glycol on the surface of the reinforced green pellets, and then dried in the shade at 15-25°C. The dried reinforced green pellets are then sintered in a box furnace, and the temperature is increased to 700°C at 5°C / min. After keeping the temperature for 1.5-2.5h, the CO2 adsorbent Li4SiO4 ceramic pellets are obtained.
[0038] The preparation method of Li4SiO4 powder is not specifically limited here.
[0039] Preferably, the Li4SiO4 powder is synthesized by solid phase method using LiOH·H2O as lithium source, nano-SiO2 as silicon source, and deionized water as solvent. Specifically, the method comprises the following steps:
[0040] Q1: LiOH·H2O and nano-SiO2 in a mass ratio of 7.35:2.5 were mixed with deionized water, and then the mixture was added to a ball mill for ball milling. The ball-to-material mass ratio was 2:1, the ball milling time was 2 h, and the ball milling speed was 200 r / min to obtain suspension 2.
[0041] Q2: The suspension 2 is placed in a constant temperature drying oven for drying at a temperature of 80-90°C for a drying time of 30-40 hours to obtain Li4SiO4 precursor powder;
[0042] Q3: Place the Li4SiO4 precursor powder in a box furnace, heat it to 700℃ at a rate of 5℃ / min and keep it warm for 2h, then pass it through a 200-mesh sieve to obtain Li4SiO4 powder.
[0043] Example 1
[0044] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0045] Weigh 3.0045 g of Li4SiO4 powder, 1.2044 g of sodium water glass with a modulus of 3.3 and a solid content of 34%, and 0.9021 g of LiOH·H2O powder, place the above raw materials in 1.2 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dropped into a beaker containing polyethylene glycol-600 at a rotation speed of 300r / min and a temperature of 70°C at a height of 3 to 4cm from the cup mouth, and the green pellets are obtained by heat preservation and curing for 5min; then the green pellets and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48h; then, the polyethylene glycol-600 is filtered to obtain reinforced green pellets, and then the reinforced green pellets are washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellets are placed in a box furnace, and the temperature is increased to 700°C at a rate of 5°C / min and kept warm for 2h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.2). Figure 1This indicates that the ceramic beads prepared by this method are pure phase Li4SiO4, but the diffraction peak is not sharp enough and the crystallinity is poor.
[0046] Example 2
[0047] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0048] Weigh 3.0015 g of Li4SiO4 powder, 1.2035 g of sodium water glass with a modulus of 3.3 and a solid content of 34%, and 0.9039 g of LiOH·H2O powder, place the above raw materials in 1.2 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dropped into a beaker containing polyethylene glycol-600 at a rotation speed of 300r / min and a temperature of 70°C at a height of 3 to 4cm from the cup mouth, and the beaker is kept warm and cured for 5min to obtain green pellets; then the green pellets and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48h; then, the polyethylene glycol-600 is filtered to obtain reinforced green pellets, and then the reinforced green pellets are washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellets are placed in a box furnace, and the temperature is increased to 700°C at a rate of 5°C / min and kept warm for 4h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.2). Figure 1 It shows that the ceramic spheres prepared by this method are pure phase Li4SiO4, with relatively sharp diffraction peaks and good crystallinity; Figure 4 It shows that the obtained adsorbent pellets have a CO2 adsorption capacity of 14.3wt.% in a pure CO2 atmosphere; Figure 5 It shows that the nitrogen adsorption-desorption curve of the adsorbent ball is a composite type II adsorption-desorption curve, BET = 1.0363m 2 / g; Figure 6 This indicates that the balls have good sphericity, and the sphericity of the width-to-length ratio is 91.86%.
[0049] Example 3
[0050] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0051] Weigh 3.0084 g of Li4SiO4 powder, 1.2068 g of sodium water glass with a modulus of 3.3 and a solid content of 34%, and 1.0211 g of LiOH·H2O powder, place the above raw materials in 1.5 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dropped into a beaker containing polyethylene glycol-600 at a rotation speed of 300 r / min and a temperature of 70°C at a height of 3 to 4 cm from the cup mouth, and the beaker is kept warm and cured for 5 minutes to obtain green pellets; then the green pellets and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48 hours; then, the polyethylene glycol-600 is filtered to obtain reinforced green pellets, and then the reinforced green pellets are washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellets are placed in a box furnace, and the temperature is increased to 700°C at a rate of 5°C / min and kept warm for 4 hours to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.3). Figure 1 It shows that the ceramic spheres prepared by this method are pure phase Li4SiO4, with sharp diffraction peaks and good crystallinity. The sphericity of the aspect ratio is 84.38% according to statistics.
[0052] Example 4
[0053] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0054] Weigh 3.0078 g of Li4SiO4 powder, 1.2035 g of sodium water glass with a modulus of 3.3 and a solid content of 34%, and 1.1421 g of LiOH·H2O powder, place the above raw materials in 1.8 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dropped into a beaker containing polyethylene glycol-600 at a rotation speed of 300r / min and a temperature of 70°C at a height of 3 to 4cm from the cup mouth, and the beaker is kept warm and cured for 5min to obtain green pellets; then the green pellets and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48h; then, the polyethylene glycol-600 is filtered to obtain reinforced green pellets, and then the reinforced green pellets are washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellets are placed in a box furnace, and the temperature is increased to 700°C at a rate of 5°C / min and kept warm for 4h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.4). Figure 1 It shows that the ceramic beads prepared by this method are pure phase Li4SiO4, with sharp diffraction peaks and good crystallinity. Figure 2 It shows that the grains on the surface of the spheres are tightly combined, with abundant pores and a grain size of about 30 μm. Figure 3 The results show that the cross-section of the ball shows the presence of sintering necks, the grain boundaries are clearly visible, the pore size is about 15μm, and the grain size is about 25μm. Figure 4 It shows that the obtained adsorbent pellets have a CO2 adsorption capacity of 22.9wt.% in a pure CO2 atmosphere. Figure 5 It shows that the nitrogen adsorption-desorption curve of the adsorbent ball is a composite type III adsorption-desorption curve, BET = 0.9520m 2 / g. The sphericity of the aspect ratio is 82.49%.
[0055] Example 5
[0056] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0057] Weigh 3.0027 g of Li4SiO4 powder, 1.2057 g of sodium water glass with a modulus of 3.3 and a solid content of 34%, and 1.2626 g of LiOH·H2O powder, place the above raw materials in 2.1 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dropped into a beaker containing polyethylene glycol-600 at a rotation speed of 300r / min and a temperature of 70°C at a height of 3 to 4cm from the cup mouth, and the beaker is kept warm and cured for 5min to obtain green pellets; then the green pellets and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48h; then, the polyethylene glycol-600 is filtered to obtain reinforced green pellets, and then the reinforced green pellets are washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellets are placed in a box furnace, the temperature is increased to 700°C at a rate of 5°C / min and kept warm for 4h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.5). Figure 1 It shows that the ceramic balls prepared by this method are pure phase Li4SiO4, with very sharp diffraction peaks and good crystallinity. Statistics show that the sphericity of the aspect ratio is 77.83%.
[0058] Comparative Example 1
[0059] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0060] Weigh 3.0045 g of Li4SiO4 powder and 1.2044 g of sodium water glass with a modulus of 3.3 and a solid content of 34%, place the above raw materials in 1.8 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry was vertically dripped into a beaker containing polyethylene glycol-600 at a speed of 300r / min and a temperature of 70°C at a height of 3-4cm from the cup mouth, and the beaker was kept warm and cured for 5min to obtain a green pellet; then the green pellet and the polyethylene glycol-600 mixture were placed in a culture dish and placed in a 50°C drying oven for secondary curing for 48h; then the polyethylene glycol-600 was filtered to obtain a reinforced green pellet, and then the reinforced green pellet was washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellet was placed in a box furnace, heated to 700°C at a rate of 5°C / min and kept warm for 4h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=3.4). The sphericity of the aspect ratio was statistically 91.33%.
[0061] Comparative Example 2
[0062] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0063] Weigh 3.0035 g of Li4SiO4 powder and 1.0228 g of PVA powder, place the above raw materials in 1.8 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dropped into a beaker containing polyethylene glycol-600 at a rotation speed of 300r / min and a temperature of 70°C at a height of 3 to 4cm from the cup mouth, and the beaker is kept warm and cured for 5min to obtain green pellets; then the green pellets and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48h; then, the polyethylene glycol-600 is filtered to obtain secondary reinforced green pellets, and then the reinforced green pellets are washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellets are placed in a box furnace, the temperature is increased to 700°C at a rate of 5°C / min and kept warm for 4h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.2), the sphericity of which is poor, and the sphericity of the aspect ratio is 47.95% according to statistics.
[0064] Comparative Example 3
[0065] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0066] Weigh 3.0040 g of Li4SiO4 powder and 0.9014 g of dextrin powder, place the above raw materials in 1.8 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dripped into a beaker containing polyethylene glycol-600 at a speed of 300r / min and a temperature of 70°C at a height of 3-4cm from the cup mouth, and the beaker is kept warm and cured for 5min to obtain a green pellet; then the green pellet and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48h; then, the polyethylene glycol-600 is filtered to obtain a reinforced green pellet, and then the reinforced green pellet is washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellet is placed in a box furnace, heated to 700°C at a rate of 5°C / min and kept warm for 4h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.2). The sphericity is poor, and the sphericity of the width-to-length ratio is 51.79% according to statistics.
[0067] Comparative Example 4
[0068] Preparation of Li4SiO4 powder: first mix LiOH·H2O and nano-SiO2 powder in a mass ratio of 7.35:2.5 with deionized water, then place the mixture in a planetary ball mill with a ball-to-material mass ratio of 2:1 and a rotation speed of 200 r / min, and ball mill for 2 h to obtain suspension 2, which is placed in a drying oven at 80°C for 36 h to obtain Li4SiO4 precursor powder, and the Li4SiO4 precursor powder is placed in a box furnace and the temperature is raised from room temperature to 700°C at a rate of 5°C / min for 2 h, and finally the calcined powder is sieved through a 200-mesh sieve to obtain Li4SiO4 powder.
[0069] Weigh 3.0078 g of Li4SiO4 powder and 1.2035 g of lithium water glass with a modulus of 4.5 and a solid content of 23%, place the above raw materials in 1.8 ml of deionized water, stir evenly to obtain a suspension 1, and place the suspension 1 in a planetary ball mill for ball milling mixing, with a ball-to-material mass ratio of 2:1, a rotation speed of 200 r / min, and a ball milling time of 1.5 h to obtain a slurry. The slurry is vertically dropped into a beaker containing polyethylene glycol-600 at a rotation speed of 300r / min and a temperature of 70°C at a height of 3 to 4cm from the cup mouth, and the beaker is kept warm and cured for 5min to obtain green pellets; then the green pellets and the polyethylene glycol-600 mixture are placed in a culture dish, and the culture dish is placed in a 50°C drying oven for secondary curing for 48h; then, the polyethylene glycol-600 is filtered to obtain secondary reinforced green pellets, and then the reinforced green pellets are washed with anhydrous ethanol and dried in the shade at room temperature; finally, the dried reinforced green pellets are placed in a box furnace, heated to 700°C at a rate of 5°C / min and kept warm for 4h to obtain Li4SiO4 ceramic pellets (lithium-silicon molar ratio Li / Si=4.2), the sphericity of which is poor, and the sphericity of the aspect ratio is 49.09% according to statistics.
[0070] The above-described embodiments are only preferred embodiments of the present invention. It should be noted that those skilled in the art may make several changes and improvements without departing from the overall concept of the present invention, and these should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing CO2 adsorbent Li4SiO4 ceramic balls, characterized in that: The method comprises at least the following steps: S1: taking a certain mass of raw materials, the raw materials comprising a certain mass ratio of Li4SiO4 powder, LiOH∙H2O powder, sodium water glass, and deionized water, and mixing the raw materials to obtain a slurry; S2: dripping the slurry obtained in step S1 into polyethylene glycol, and obtaining green pellets after high-temperature curing; S3: placing the mixture of the green pellets and polyethylene glycol in a constant temperature environment for secondary curing, and then filtering and washing to obtain reinforced green pellets; S4: The reinforced green pellets obtained in step S3 are dried in the shade and sintered to obtain CO2 adsorbent Li4SiO4 ceramic pellets.
2. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 1, characterized in that: In step S1, the mass ratio of Li4SiO4 powder, LiOH∙H2O powder, sodium water glass and deionized water is 10:(3~4.6):(4~8):(4~7), and the LiOH∙H2O powder in the raw material is obtained by sieving with 200 mesh.
3. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 2, characterized in that: In step S1, Li4SiO4 powder, LiOH∙H2O powder and sodium water glass are added to deionized water and stirred evenly to obtain a suspension 1. Subsequently, the suspension 1 is added to a ball mill for ball milling at a speed of 200 r / min for 1 to 2.5 h to obtain a slurry.
4. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 3, characterized in that: The polyethylene glycol in step S2 is placed in a constant temperature open container and is in a stirring state, the temperature is 50-80 ° C, the rotation speed is 300 r / min, and then each drop of slurry with a volume of 0.03-0.04 ml is dripped into the polyethylene glycol, and the vertical distance between the slurry drop and the top of the container is 3-4 cm. After the dripping is completed, the biscuit is kept warm for 5 minutes to obtain the green pellet.
5. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 4, characterized in that: In step S3, the mixture containing the green pellets and polyethylene glycol is placed in a culture dish and secondary cured in a 50° C. constant temperature drying oven for 40 to 50 h to obtain reinforced green pellets.
6. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 5, characterized in that: In step S3, the reinforced green pellets are washed with anhydrous ethanol and then dried in the shade at 15-25°C. The dried reinforced green pellets are then sintered in a box furnace, heated to 700°C at 5°C / min, and kept at this temperature for 1.5-2.5 hours to obtain CO2 adsorbent Li4SiO4 ceramic pellets.
7. A method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to any one of claims 1 to 6, characterized in that: The preparation method of the Li4SiO4 powder comprises the following steps: Q1: LiOH∙H2O and nano-SiO2 were mixed with deionized water in a certain mass ratio, and then added into a ball mill for 2 h to obtain suspension 2; Q2: The suspension 2 is placed in a constant temperature drying oven at 80-90 °C for 30-40 h to obtain Li4SiO4 precursor powder; Q3: Place the Li4SiO4 precursor powder in a box furnace, heat it to 700 ℃ at 5 ℃ / min and keep it at this temperature for 2 h to obtain Li4SiO4 powder.
8. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 7, characterized in that: The mass ratio of LiOH∙H2O to nano-SiO2 in step Q1 is 7.35:2.
5.
9. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 7, characterized in that: In step Q1 and step S1, the ball-to-material mass ratio in the ball mill is 2:1, and the ball mill speed is 200 r / min.
10. The method for preparing a CO2 adsorbent Li4SiO4 ceramic ball according to claim 7, characterized in that: The Li4SiO4 powder is obtained by sieving through a 200-mesh sieve.
Citation Information
Cited By
Method for preparing ceramic microbeads based on environment-friendly non-aqueous gel system
CN120004601A
Method for preparing ceramic microspheres based on an environmentally friendly non-aqueous gel system
CN120004601B